Los desafíos vivenciados por los profesores no indígenas em la Escuela Indígena Parintintin - Kellyane Lisboa Ramos; Eulina Maria Leite Nogueira; Zilda Gláucia Elias Franco (Universidade Federal de Rondônia, 2019)
This article aims to analyze the challenges faced by non - indigenous teachers who work in an indigenous school; emphasize the historical trajectory of teacher education; to contextualize the relationship between indigenous school education and the work of non-indigenous teachers; to reflect on the need for greater interventions and discussions on diversity issues in training courses. Faced with this problem addressed to non-indigenous teachers, we seek to answer the following question: do non-indigenous teachers feel prepared to teach in culturally differentiated environments? Do you have enough knowledge about cultural diversity that could guide your practice? In the search for answers, an interview was conducted with 03 non-indigenous teachers who teach at the Parintintin indigenous school, located in the Pupunha Village in Humaitá-AM. As a qualitative approach both to guide research and to analyze the data, it is considered through the results that the teachers addressed have many challenges in relation to their practice in this context, which comes from the unstructured adequate school, lack of basic materials to assist the teacher and student, a curriculum that does not meet the needs of the indigenous culture, and an initial formation that did not "prepare" enough for praxis linked to cultural diversity.